2006
DOI: 10.1186/1471-2407-6-233
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution analysis of HLA class I alterations in colorectal cancer

Abstract: Background: Previous studies indicate that alterations in Human Leukocyte Antigen (HLA) class I expression are frequent in colorectal tumors. This would suggest serious limitations for immunotherapy-based strategies involving T-cell recognition. Distinct patterns of HLA surface expression might conceal different immune escape mechanisms employed by the tumors and are worth further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The β2m gene mutations may be preferentially selected by T cell selective pressure. In this regard, the impairment of HLA class I antigen expression is a frequent even in MSI (+) colon carcinoma [140] and predominantly mediated by frameshift mutations of the β2m gene [137, 141, 142] likely reflecting immunoselective pressure. In view of these findings, the outgrowth of MSI (+) colon carcinoma cells that lack HLA class I as well as class II antigen expression is compatible with the selection of HLA class I and class II antigen-deficient tumor cells during MSI (+) colon carcinoma tumorigenesis.…”
Section: Role Of Immune Selective Pressure In the Hla Antigen And Nkcmentioning
confidence: 99%
“…The β2m gene mutations may be preferentially selected by T cell selective pressure. In this regard, the impairment of HLA class I antigen expression is a frequent even in MSI (+) colon carcinoma [140] and predominantly mediated by frameshift mutations of the β2m gene [137, 141, 142] likely reflecting immunoselective pressure. In view of these findings, the outgrowth of MSI (+) colon carcinoma cells that lack HLA class I as well as class II antigen expression is compatible with the selection of HLA class I and class II antigen-deficient tumor cells during MSI (+) colon carcinoma tumorigenesis.…”
Section: Role Of Immune Selective Pressure In the Hla Antigen And Nkcmentioning
confidence: 99%
“…While the loss of MHC class I expression in human tumors is not definitive evidence of immunoediting, this widely observed defect remains some of the best to date. Loss of MHC class I in human tumors is frequently observed in several cancers including B cell lymphomas, colorectal, ovarian, breast, melanoma, lung and renal cancers [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113]. Ongoing studies continue to define the molecular mechanisms of downregulation of MHC molecules.…”
Section: C122 Editing For Reduced Mhc and Antigen Expression And mentioning
confidence: 99%
“…Various studies have identified HLA alterations in colorectal cancer [19-21], including the prevalence of HLA class I alterations in MSI-H tumors [8,22]. However, the latter studies did not compare the frequency of alterations between hereditary and sporadic MSI-H tumors neither the mechanisms that led to HLA class I alterations in each subgroup.…”
Section: Introductionmentioning
confidence: 99%